1971
DOI: 10.1620/tjem.104.215
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Adsorption of Vitamin B<sub>12</sub> to Intestinal Mucosa Homogenate of Adult and Unweaned Rats

Abstract: Studies on the Adsorption of Vitamin. B12 to Intestinal Mucosa Homogenate of Adult and Unweaned Rats. Tohoku J. exp. Med., 1971, 104 (3), [215][216][217][218][219][220][221][222][223] For the purpose of elucidat ing the physiological significance of intrinsic factor (IF) in vitamin B12 absorption, comparative studies on the adsorption of vitamin B12 to intestinal mucosa homogenate of unweaned (aged 48 hours old) and adult rats were carried out. Any material having IF activity on the intestine of the adult rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1972
1972
2002
2002

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…vitamin B1, absorption; intrinsic factor In our preceding papers (Yamada et al 1970(Yamada et al , 1971), we reported the results obtained by comparative studies on the adsorption of vitamin B12 to intestinal mucosa homogenates of adult and unweaned rats (48 hours after birth). The data obtained indicated that 1) stomach of the unweanded rats secreted neither intrinsic factor (IF) nor IF-like materials, 2) the amount of vitamin B12 adsorbed to the intestinal mucosa homogenates of the unweaned rats in the absence of IF was very high compared with that to the intestinal mucosa homogenates of the adult rats, and 3) adsorption of vitamin B12 to the intestinal mucosa homogenates of the unweaned rats was not significantly affected by the omission of bivalent cations from the incubation medium.…”
mentioning
confidence: 99%
“…vitamin B1, absorption; intrinsic factor In our preceding papers (Yamada et al 1970(Yamada et al , 1971), we reported the results obtained by comparative studies on the adsorption of vitamin B12 to intestinal mucosa homogenates of adult and unweaned rats (48 hours after birth). The data obtained indicated that 1) stomach of the unweanded rats secreted neither intrinsic factor (IF) nor IF-like materials, 2) the amount of vitamin B12 adsorbed to the intestinal mucosa homogenates of the unweaned rats in the absence of IF was very high compared with that to the intestinal mucosa homogenates of the adult rats, and 3) adsorption of vitamin B12 to the intestinal mucosa homogenates of the unweaned rats was not significantly affected by the omission of bivalent cations from the incubation medium.…”
mentioning
confidence: 99%